Peningkatan Potensi Kelompok Tunagrahita melalui Program Budidaya Tanaman di Desa Karangpatihan Ponorogo Jawa Timur - Dhika Amalia Kurniawan; Muhammad Ridlo Zarkasy; Hayatul Maemunah; Muhammad Muhammad (Warta LPM, 2022)
Partners in this community service is a Tunagrahita group in Karangpatihan Village, Balong Ponorogo. The main problem by partners is weakness in thinking, acting, and socializing with the community so that they are unable to work and unable to make ends meet. This was due to the food crisis in 1967. This condition took place over the years so resulted in the disabled people being unable to work like normal people, resulting in economic disability. To fulfill their daily needs, the Tunagrahita depend their economy on assistance from other parties (social assistance), both from the general public and assistance from the government in order to survive. Seeing these problems, the PKM team tried to provide solutions to help meet the economic needs of Tunagrahita by increasing its potential both in terms of knowledge and skills by farming such as cultivating vegetables using polybag planting media. The products produced are daily needs of the community, namely capsicum, frutescens, brassica rapa, V. unguiculata and S. lycopersicum. The method in this activity is participatory training through training, mentoring and evaluation of the program being implemented. The purpose of this service is to help the Tunagrahita community groups to improve in terms of economy, social and knowledge so that the Tunagrahita can get income to meet their needs without having to continually depend on their economy on the help of other parties. The results of this dedication are that currently 1) the Tunagrahita are starting to be able to cultivate crops., 2) the Tunagrahita are starting to be able to pack and branding of their crops and begin to be able to sell to the nearest market or shop, and 3) Tunagrahita have not been able to make simple bookkeeping of the results of plant cultivation products because of their low Intellectual Quotient (IQ) level because from the start they are not familiar with literacy.